Structure of Foot-and-mouth disease virus serotype A10 61 alone and complexed with oligosaccharide receptor: receptor conservation in the face of antigenic variation. - Fry, E; Newman, J; Curry, S; Najjam, S; Jackson, T; Blakemore, W; Lea, S; Miller, L; Burman, A; King, A; Stuart, D (2005)
Foot-and-mouth disease viruses (FMDVs) target epithelial cells via integrin receptors, but can acquire the capacity to bind cell-surface heparan sulphate (or alternative receptors) on passage in cell culture. Vaccine viruses must be propagated in cell culture and, hence, some rationale for the selection of variants in this process is important. Crystal structures are available for type O, A and C viruses and also for a complex of type O strain O(1)BFS with heparin. The structure of FMDV A10(61) (a cell culture-adapted strain) complexed with heparin has now been determined. This virus has an RGSD motif in place of the otherwise conserved RGD integrin-binding motif and the potential to bind heparan sulphate (suggested by sequence analyses). FMDV A10(61) was closely similar in structure to other serotypes, deviating most in antigenic sites. The VP1 GH loop comprising the integrin-binding motif was disordered. Heparin bound at a similar site and in a similar conformation to that seen in the analogous complex with O(1)BFS, although the binding had a lower affinity and was more ionic.